Information and communication technologies management in turbulent business environments - Koh, S. C. L. (S. C. Lenny) (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
In today's world, widespread change in business and technology creates a dynamic and chaotic work environment, pushing intelligent use of information communication technologies (ICTs) to succeed. This book informs today's business managers of important ICT strategy in changing business environments, techniques for effective ICT development, and ICT challenges for the future. A research publication for practitioners, researchers, and academicians, this book covers topics such as e-technology, knowledge management, and security and risk management.